i-Home financing calculator / Dr. Shafinar Ismail … [et al.] - Ismail, Dr. Shafinar; Razak, Tajul Rosli; Md Sahiq, Aqilah Nadiah; Mohd Rafien, Nor Shahrina; Idris, Nur Hafidzah (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2013)
The product is called "i-Home Financing Calculator". The letter "i" stands for "innovative". We would like to develop this calculator to provide information to the borrowers (especially prospective home buyers) on the price of a house that a buyer can afford. Currently, the existing home loan calculator is very general where the potential borrowers could only know the estimated monthly instalment that they need to commit if they want to obtain a housing loan. But, the potential borrowers could not specifically know on their loan eligibility. In order to know on the eligibility of obtaining a home loan, it is only known when their applications are being processed by the banks which often take time and need a lot of documentations. As a result, borrowers could not rely on the existing home loan calculator when making loan decision as the current calculator is very basic and simple. Thus, we would like to develop better home financing calculator to assist the borrowers in making loan decision. By improving the current home loan calculator, potential borrowers can easily check the total monthly instalment and at the same time, knowing their maximum entitlement of the housing loan; after considering monthly commitments with the banks (e.g. credit card repayment, personal loan and car loan). The calculator is also useful for borrowers who are considering on refinancing their current housing loan.